Perception on the effectiveness of electronic word-of-mouth as a marketing tool of Pamantasan ng Lungsod ng Maynila - Business School Student - Dumape, Alleiah Valerie A., Mascardo, Jamelyn P., Nadurata, Chrysley M., Regulado, Marjelyn L., Rodriguez, Gianna Lesha S. 4 0 16; 5
Abstract An old method used in marketing is conveying information through traditional word-of-mouth in which referrals and recommendations come from families, friends, colleagues, and other people one interacts with. However, the emergence of the Internet paved the way for the spread of electronic word-of-mouth (eWOM), which is considered a new form of WOM. The objective of this paper is to: (1) investigate the perception of Pamantasan ng Lungsod ng Maynila - Business School Students on the effectiveness of electronic word-of-mouth as a marketing tool; (2) analyze the underlying factors that affect the effectiveness of eWOM, and; (3) contribute to the existing body of knowledge on eWOM by formulating a comprehensive understanding of the topic due to the lack of related studies This study utilized a descriptive research design to collect data and mitration using a survey questionnaire and the distribution is only limited to Pamantasan ng Lungsod ng Maynila - Business School Students. Furthermore, the researchers used the quantitative research method to analyze the data gathered during the study. The data obtained shows that most of the respondents came from the BS Accountancy course, being in the range of 20-21 age group that are mostly female students with monthly allowances below P1,000. Results showed that the most encountered eWOM by PLMBS Students is online reviews. The respondents consider message credibility, eWOM quantity, and visual evidence as highly effective factors that affect the effectiveness of eWOM. The study aims to provide practical recommendations to marketers to tap into the influential nature of online recommendations by embracing eWOM platforms, encourage online and non-online consumers to post reviews with images and videos as other consumers use them as a basis to make informed decisions, and allow future researchers to leverage the limitations highlighted in this study to identify areas for improvement. Keywords: eWOM, Marketing Tool, and Online Reviews
Business Research: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2